Matrix Mixed Inequalities (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we prove that all the eigenvalues of arbitrarily complex matrix are located in one closed disk, which is a refinement of some existing inequalities.
Keywords: 47A30; 15A42; 15A18